Philosophy of Law in Legal Reality - Irman Syahriar; Benhard Kurniawan Pasaribu; Dina Paramitha Hefni Putri; Khairunnisah Khairunnisah (International Journal Labs, 2023)
In recent decades, the phenomenon of disobedience or even 'harassment' of the law has been rife. Both in terms of action and giving court decisions are often considered unwise because they do not provide satisfaction to people who are experiencing legal problems. The judge is considered to no longer give a fair verdict on the initial process to the end of the ongoing trial, including due to court procedures that are not in accordance with legal provisions. As stated by Bismar Siregar, currently many cases are decided based on certain 'orders' through cooperation between law enforcement officials (oknum) and perpetrators of law violations who with their intelligence are able to distort the meaning of the rule of law with the opinion of judges. Researchethode is a type of normative legal research or research using the rules in existing laws and regulations and research carried out by collecting data directly in the field from competent parties related to the object studied because it is in the form of secondary data such as legislation and literature books. A judge's decision that reflects justice is not easy to find a benchmark for disputing parties. Because fair to one party is not necessarily fair to the other. The duty of the judge is to uphold the acidity in accordance with the trash made at the head of the judgment which reads